Feasibility of Pedal Access for Geniculate Artery Embolization - Hasan, Eusha; Saifuddin, Ali; Schuchardt, Philip; Khoury, Joe; Al-Roubaie, Mustafa (Journal of Clinical Interventional Radiology ISVIR, 2025)
Geniculate artery embolization is a treatment option for refractory knee osteoarthritis in patients unable to receive total knee arthroplasty. This case report describes two patients for whom pedal access was used to embolize the geniculate arteries due to challenging groin anatomy secondary to significant comorbidities (morbid obesity, proximal atherosclerosis). Both patients achieved marked pain relief and enhanced knee function at 1-month follow-up. These cases suggest that pedal access is a viable alternative, offering a promising approach for patients with unfavorable anatomy and comorbidities that make groin access impractical. Further research is needed to validate these findings in larger patient populations.
Keywords: geniculate; embolization; osteoarthritis